2021
DOI: 10.3389/fsufs.2021.663445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen and Seeding Rate on β-Glucan, Protein, and Grain Yield of Naked Food Barley in No-Till Cropping Systems in the Palouse Region of the Pacific Northwest

Abstract: Barley (Hordeum vulgare L.) has a storied history as a food crop, and it has long been a dietary staple of peoples in temperate climates. Contemporary research studies have focused mostly on hulled barley for malt and animal feed. As such, nitrogen (N) and seeding rate agronomic data for naked food barley are lacking. In this study, we evaluated the effects of N on ß-glucan and protein content, and N and seeding rate on phenotypic characteristics of naked food barley, including grain yield, emergence, plant he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
2
7
0
Order By: Relevance
“…Habiyaremye et al. (2021) suggest that β‐glucan is related more to environmental factors, such as precipitation and temperature, than to fertility, as they found higher β‐glucan associated with increased rainfall and lower temperatures. These results are contrary to what has been generally reported in the literature, where β‐glucan content is said to increase under hotter, drier conditions (Meints & Hayes, 2019; Meints et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Habiyaremye et al. (2021) suggest that β‐glucan is related more to environmental factors, such as precipitation and temperature, than to fertility, as they found higher β‐glucan associated with increased rainfall and lower temperatures. These results are contrary to what has been generally reported in the literature, where β‐glucan content is said to increase under hotter, drier conditions (Meints & Hayes, 2019; Meints et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Habiyaremye et al. (2021) also conducted a study in the Palouse region and found that location had a significant effect on β‐glucan but not on protein content. Regarding β‐glucan stability, results from Choi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen (N) availability in the soil is the main factor influencing β-glucan content in cereals (Güler, 2003b;Dvončová et al, 2010). It was reported that mineral N fertilizers increase the β-glucan content (Güler, 2003a;Noworolnik et al, 2014;Habiyaremye et al, 2021), particularly when they are fertilized with 100 kg N ha −1 (for wheat) and 80 kg N ha −1 (for barley; Güler, 2003a) regardless of the fact that β-glucan location in the grain among compared cereal grains is different (mostly in aleurone layer for wheat and endosperm for barley; Izydorczyk and MacGregor, 2000;Lazaridou and Biliaderis, 2007). On the other hand, β-glucan content of rye, wheat, barley, and oat obtained from organic farming was comparable with those from conventional farming (Menkovska et al, 2017), indicating that β-glucan content can be associated with grain size and yield (Güler, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Naked barley has a great potential as functional food for humans and highquality feed for animals (Yang et al, 2018;Habiyaremye et al, 2021). It is characterized by high protein content and many other important nutrients (Shaveta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%